Intramolecular arsanilazotyrosine-248-Zn complex of carboxypeptidase A: a monitor of multiple conformational states in solution. - Harrison, L W (1975)
The red azoTyr-248-Zn complex of arnilazocarboxypeptidase, previously used to demonstrate differences in conformation of the enzyme in crystals and in solution, has now provided means to detect multiple conformations of the enzyme in solution by stopped-flow pH and temperature jump experiments. These studies identify two distinct processes. Er + H+ in equilibrium Ey (I), is the extremely rapid, Kfast about 10(5) sec-1, pH dependent dissociation of the metal complex. Ey in equilibrium Ey' (II), is much slower, Kslow about 5 sec-1, pH independent interconversion of two distinct populations of protein molecules, Ey and Ey', in which the yellow azo-Tyr-248 is different conformations. These two conformations can be differentiated readily by stopped-flow pH-jump experiments, since I is three to four orders of magnitude faster than II. Mathematical expressions derived from this mechanism accurately predict all observations over the pH range from 6.0 to 8.5. In a previous stopped-flow pH-jump experiment, Lipcomb and coworkers [Quiocho, F. A., McMurray, C. H. & Lipcomb, W. H. (1972), Proc. Nat. Acad. Sci. USA 69, 2850-2854] recognized only a single process with a rate constant of about 6 sec-1, but not the major, very rapid rate observed here. The failure to detect this fast process led to the postulation of a number of explanations intended to account for the detection of only a single, slow rate. The present observations show that the premise for those conjectures is not valid. The azoprobe reveals the existence of rapidly interconvertible substructures of carboxypeptidase A, and the results support the view that in solution, enzymes can adopt multiple, readily interconvertible and related conformations which could then either facilitate or impede catalysis. In crystals, rearrangement of molecular structure could be severely impaired or restricted, and crystallization might single out either active or inactive conformations. In the latter case, such crystals would have greatly reduced activities and markedly altered catalytic behavior, as is observed for carboxypeptidase A. In combination with detailed kinetic analysis of crystals, conformational analysis in solution should be a valuable guide to discern enzyme mechanisms and select crystals for x-ray structure analysis.